2018
DOI: 10.1103/physrevlett.120.057201
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Spin Liquids in Frustrated Spin-1 Diamond Antiferromagnets

Abstract: Motivated by the recent synthesis of the spin-1 A-site spinel NiRh2O4, we investigate the classical to quantum crossover of a frustrated J1-J2 Heisenberg model on the diamond lattice upon varying the spin length S. Applying a recently developed pseudospin functional renormalization group (pf-FRG) approach for arbitrary spin-S magnets, we find that systems with S ≥ 3/2 reside in the classical regime where the low-temperature physics is dominated by the formation of coplanar spirals and a thermal (order-by-disor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 32 publications
1
87
0
Order By: Relevance
“…The preservation of fermion number constraint within pf-FRG has been numerically demonstrated in Ref. 32 (see also Ref. 25 for more details).…”
Section: B Parametrization Of the Vertexmentioning
confidence: 83%
“…The preservation of fermion number constraint within pf-FRG has been numerically demonstrated in Ref. 32 (see also Ref. 25 for more details).…”
Section: B Parametrization Of the Vertexmentioning
confidence: 83%
“…An early theoretical study [25] of NiRh 2 O 4 considered a model with antiferromagnetic (AFM) first and secondneighbor Heisenberg exchanges (J 1 and J 2 ), applicable to frustrated spinels, and proposed that the non-magnetic ground state might arise from large single-ion anisotropy DS 2 z , with D>0 favoring local S z =0. A pseudospin functional renormalization group study of the J 1 -J 2 model [26] found that while the S = 1 case favors a quantum spiral spin liquid ground state, the impact of tetragonal distortion or large D/J 1 > ∼ 8 is to respectively favor Néel order or the S z =0 ground state. Both studies effectively ignored orbital degrees of freedom.…”
mentioning
confidence: 99%
“…Two paradigmatic systems harboring spiral spin liquids are the Heisenberg models on the two-dimensional honeycomb and the three-dimensional diamond lattice with nearest neighbor J 1 and antiferromagnetic second neighbor J 2 > 0 couplings. [13][14][15][16][17] Even though these systems are bipartite and, hence, show unfrustrated ferromagnetic or Néel magnetic order in the J 1 -only case, when J 2 > 0 is tuned beyond a certain critical coupling ratio J 2 /|J 1 |, spiral contours or surfaces begin to form marking the onset of a spiral spin liquid. Various numerical studies indeed indicate that both models retain their non-magnetic ground states when replacing the classical S → ∞ spins by quantum S = 1/2 spins possibly realizing a quantum spin-liquid phase.…”
Section: Introductionmentioning
confidence: 99%